2022
DOI: 10.1097/ccm.0000000000005765
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Socioeconomic Status and Outcomes in Critical Care: A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES: Socioeconomic status is well established as a key determinant of inequalities in health outcomes. Existing literature examining the impact of socioeconomic status on outcomes in critical care has produced inconsistent findings. Our objective was to synthesize the available evidence on the association between socioeconomic status and outcomes in critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
1
10
1
Order By: Relevance
“…The local electronic medical record at each site was queried to obtain the patient address (at the time of admission if possible), as well as primary payor and primary language spoken for each admission. Each of these indices, as well as race and ethnicity, have been shown to be relevant to health delivery and outcomes in acutely ill children and were thus considered important to evaluate for a possible association with PICU outcomes (3, 10, 12, 24–35). Addresses were mapped to census tract and subsequently assigned nationally normed overall COI categories of very low, low, moderate, high, or very high as well as a continuous ordinal variable (0–100) of neighborhood opportunity using the COI 2.0 (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The local electronic medical record at each site was queried to obtain the patient address (at the time of admission if possible), as well as primary payor and primary language spoken for each admission. Each of these indices, as well as race and ethnicity, have been shown to be relevant to health delivery and outcomes in acutely ill children and were thus considered important to evaluate for a possible association with PICU outcomes (3, 10, 12, 24–35). Addresses were mapped to census tract and subsequently assigned nationally normed overall COI categories of very low, low, moderate, high, or very high as well as a continuous ordinal variable (0–100) of neighborhood opportunity using the COI 2.0 (16).…”
Section: Methodsmentioning
confidence: 99%
“…admission if possible), as well as primary payor and primary language spoken for each admission. Each of these indices, as well as race and ethnicity, have been shown to be relevant to health delivery and outcomes in acutely ill children and were thus considered important to evaluate for a possible association with PICU outcomes (3,10,12,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) Exploratory analyses were performed evaluating 1) using PRISM III for severity of illness adjustment, 2) the COI subdomains (education, health and environment, social and economic), and 3) the period from March to December 2020 during which epidemiology of PICU admissions was different (28). Post hoc pairwise analyses were also performed between all COI categories when a statistically significant difference was identified for severity of illness and other clinical characteristics, with Bonferroni correction for multiple comparisons.…”
Section: Research In Contextmentioning
confidence: 99%
“…Racial disparities were highlighted in a systematic review that observed higher mortality rates, greater financial burden, and differences in quality of care for Black patients admitted to the ICU when compared with White patients (11). Higher mortality was also noted in a meta-analysis following ICU admission in patients with lower socioeconomic status (12). More recent studies have observed increased mortality in Black and Hispanic populations during the COVID-19 pandemic (13).…”
mentioning
confidence: 99%
“…Internationally, healthcare systems are experiencing ED overcrowding [2], including those in the UK where the worst waiting times on record have been recently reported [3]. It is known that socioeconomic deprivation is associated with poor health outcomes across both chronic and critical illness [4,5], but the sociodemographic factors associated with delays to hospital admission from the ED are poorly understood. Knowledge of factors associated with delays to admission may be useful in addressing their underlying cause and mitigating adverse outcomes.…”
mentioning
confidence: 99%
“…Other pathways to hospital admission exist, notably via referral from primary care physician directly to an inpatient unit, and as such this study does not capture every hospital admission. While area-level markers of socioeconomic status have been shown to be robust predictors of outcomes in the critically ill [5], it is important to note that variation in the socioeconomic profile of individuals may differ from that ascribed to their area of residence. Socioeconomic status, female sex, and hospital site are associated with very long delays to admission from the ED.…”
mentioning
confidence: 99%